Проектирование систем логического управления с использованием модели темпорального автомата - Малахов, Н. В. (ХНУРЕ, 2019)
Approaches to the design of logical control systems are discussed in the given work. Particular attention is paid to the benefits of the implementation of the device on a programmable logic integrated circuit. The concepts of finite state automata and timed automata are analyzed in the work. A Moore finite state automata model construction method for a given digital control system is proposed. The method involves using of a counter to implement clock constraints.